Surface morphology and structural types of natural impact apographitic diamonds - Kvasnytsya, V.; Wirth, R.; Piazolo, S.; Jacob, D.E.; Trimby, P. (Сверхтвердые материалы, 2016)
External and internal morphologies of natural impact apographitic diamonds (paramorphoses) have been studied. Вивчено зовнішню і внутрішню морфологію природного імпактного апографітового алмазу – параморфоз. Изучена внешняя и внутреняя морфология природного импактного апографитового алмаза – параморфоз.